Real-time dual-loop electric current measurement for label-free nanofluidic preconcentration chip. Issue 1 (5th November 2014) - Chung, Pei-Shan; Fan, Yu-Jui; Sheen, Horn-Jiunn; Tian, Wei-Cheng
Abstract : A label-free approach to preconcentrating (bio)molecules and monitoring the multibehavior molecular plug through real-time dual-loop electric current monitoring. Abstract : An electrokinetic trapping (EKT)-based nanofluidic preconcentration device with the capability of label-free monitoring trapped biomolecules through real-time dual-loop electric current measurement was demonstrated. Universal current–voltage ( I – V ) curves of EKT-based preconcentration devices, consisting of two microchannels connected by ion-selective channels, are presented for functional validation and optimal operation; universal onset current curves indicating the appearance of the EKT mechanism serve as a confirmation of the concentrating action. The EKT mechanism and the dissimilarity in the current curves related to the volume flow rate ( Q ), diffusion coefficient ( D ), and diffusion layer (DL) thickness were explained by a control volume model with a five-stage preconcentration process. Different behaviors of the trapped molecular plug were categorized based on four modes associated with different degrees of electroosmotic instability (EOI). A label-free approach to preconcentrating (bio)molecules and monitoring the multibehavior molecular plug was demonstrated through real-time electric current monitoring, rather than through the use of microscope images.